The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s42003-018-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of non-tandemly repeated rDNAs and their intragenomic heterogeneity in Rhizophagus irregularis

Abstract: Arbuscular mycorrhizal fungus (AMF) species are some of the most widespread symbionts of land plants. Our much improved reference genome assembly of a model AMF, Rhizophagus irregularis DAOM-181602 (total contigs = 210), facilitated a discovery of repetitive elements with unusual characteristics. R. irregularis has only ten or 11 copies of complete 45S rDNAs, whereas the general eukaryotic genome has tens to thousands of rDNA copies. R. irregularis rDNAs are highly heterogeneous and lack a tandem repeat struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 91 publications
(121 reference statements)
3
69
0
Order By: Relevance
“…The taxonomic resolution with at least SSU sequences, used in a well-maintained reference database for AMF (Öpik and Davison, 2016), is thought to be similar (i.e., at least at the genera level but not at the species or finer clade) to that of morphological delimitation (Davison et al, 2015). Importantly, however, the longer-read-length PacBio sequencing of the R. irregularis genome suggested the presence of intra-isolate variation in the rRNA genes (Maeda et al, 2018). Whether this variation is commonly observed in AMF and its biological effects are unclear; however, the finding suggests the need to re-evaluate the resolution power of commonly used DNA-based delimitation of AMF species.…”
Section: A Mosaic Of Amf Is Responsible For Phosphate Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomic resolution with at least SSU sequences, used in a well-maintained reference database for AMF (Öpik and Davison, 2016), is thought to be similar (i.e., at least at the genera level but not at the species or finer clade) to that of morphological delimitation (Davison et al, 2015). Importantly, however, the longer-read-length PacBio sequencing of the R. irregularis genome suggested the presence of intra-isolate variation in the rRNA genes (Maeda et al, 2018). Whether this variation is commonly observed in AMF and its biological effects are unclear; however, the finding suggests the need to re-evaluate the resolution power of commonly used DNA-based delimitation of AMF species.…”
Section: A Mosaic Of Amf Is Responsible For Phosphate Uptakementioning
confidence: 99%
“…This may lead to the acceptance of concepts of biological species (De Queiroz, 2005) in AMF as well as in many other organisms and to prediction of the phenotypic similarity within the same AMF species. Moreover, finding of the presence of intra-isolate heterologous rRNA genes may solve the problem of the complex genomic organization of AMF (Maeda et al, 2018). In addition, it is observed that isolates of the same AMF species undergo anastomosis and exchange nuclei (Croll et al, 2009;Sbrana et al, 2018).…”
Section: Perspective: How Do We Know About Dynamic Mycorrhizal Phosphmentioning
confidence: 99%
“…The SPX domain acts by allowing the binding of the regulatory protein with inositol polyphosphates (InsPs), thus modulating its activity in a phosphate-dependent manner [38]. Recent mining of the published genomic and transcriptomic data from AMFs detected the presence of genes encoding for SPX domain-containing proteins and for InsPs metabolic enzymes [37,39]. Some of them have been found to be regulated upon polyP formation and in the response to high phosphate concentrations.…”
Section: The First Part Of the Story: The Fungus Provides The Plant Hmentioning
confidence: 99%
“…Recent studies into single-nucleus sequencing of some AMF culture lines demonstrated the presence of not only homokaryons but also dikaryons and heterokaryons [61,62]. Furthermore, long-read whole-genome sequencing of R. irregularis DAOM197198 indicated that the genome contained 10 different rDNA sequences that were scattered (i.e., non-tandem repeats) around the chromosome [63]. These findings mitigate against the use of rDNA sequences to identify individual AM species in field AMF infection units, as a one-to-one relationship may not be applicable to the rDNA sequences and the genetic identities of the individual component species.…”
Section: Resultsmentioning
confidence: 99%